Eine neue Adressierungsart: Positionsadressierung bei indexikalischen Angaben und funktionalen Angabezusätzen - Wiegand, Herbert Ernst (Lexikos, 2015)
A New Type of Addressing: Positional Addressing at Indexical Items and Functional Item Additions. Following a brief reminder of the most important concepts from the metalexicographic discourse of the past twenty five years, a new type of addressing is introduced. This is the positional addressing of indexical items, e.g. items indicating syllable division and items indicating the detachability of particle verbs as well as that of functional item additions, which expand items internally, e.g. omission and end of verse indicators. The hypothesis is further presented that non-typographical structural indicators are also positionally addressed. The supposition of positional addressing contributes to a more precise understanding of the information retrieval of the active user. Finally it is shown that the consideration of positional addressing contributes to the differentiation of article structures where an addressing relation is defined with regard to their structure-carrying set.